Independensi Memoderasi Pengaruh Akuntabilitas dan Integritas Pada Kualitas Audit (Studi Empiris Pada KAP Provinsi Bali) - Dewi, A.A. Istri Muthia; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 24 No 1 (2018)DO - 10.24843/EJA.2018.v24.i01.p20, 2018)
This study aims to obtain empirical evidence of the influence of accountability and integrity on audit quality, as well as the ability of independence to strengthen the effect of accountability, and integrity on audit quality. The research was conducted at the Public Accounting Firm of Bali Province registered with the Indonesian Institute of Certified Public Accountants. The number of samples used counted 41 people by using purposive sampling technique. Data collection method was done by using questionnaire method and data analysis technique used is multiple linear regression analysis and moderated regression analysis. Based on the analysis found that accountability has positive effect on audit quality. Integrity has a positive effect on audit quality. Independence is unable to strengthen the effect of accountability on audit quality. Independence strengthens the influence of integrity on audit quality   Keywords: independence, accountability, integrity, and audit quality. This study aims to obtain empirical evidence of the influence of accountability and integrity on audit quality, as well as the ability of independence to strengthen the effect of accountability, and integrity on audit quality. The research was conducted at the Public Accounting Firm of Bali Province registered with the Indonesian Institute of Certified Public Accountants. The number of samples used counted 41 people by using purposive sampling technique. Data collection method was done by using questionnaire method and data analysis technique used is multiple linear regression analysis and moderated regression analysis. Based on the analysis found that accountability has positive effect on audit quality. Integrity has a positive effect on audit quality. Independence is unable to strengthen the effect of accountability on audit quality. Independence strengthens the influence of integrity on audit quality   Keywords: independence, accountability, integrity, and audit quality.